Effect of hope therapy on general self-efficacy among substance abusers - Zahra Saboor; Tayebe Rahimi Pordanjani; Ali Mohammadzadeh Ebrahimi (Gonabad University of Medical Sciences, 2019)
The variety and prevalence of substance abuse are growing and its consequences on physical and psychological health, as well as, on global social and economic concerns are heavy. General self-efficacy is a critical factor underlying substance abuse and its successful treatment. The present study was aimed to investigate the effect of hope therapy on general self-efficacy among substance abusers. This study was quasi-experimental with pretest-posttest and control group. The statistical population comprised all of the substance abusers who referred to addiction treatment centers. Convenience sampling method was used to select 40 participants among volunteers. The participants randomly were assigned into the experimental and control groups. The experimental group received eight sessions of two-hour of hope therapy. Both groups responded to general self-efficacy scale before and after the treatment. There was a significant improvement in general self-efficacy of substance abusers after hope therapy sessions. According to research findings, using of hope therapy could have important role in increasing the general self-efficacy of substance abusers and thereby can lead to successful treatment programs and other positive outcomes in the treatment of substance abuse.